2023
DOI: 10.46234/ccdcw2023.034
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Gestational Weight Gain for Women with Gestational Diabetes Mellitus — China, 2011–2021

Abstract: What is already known about this topic?Joint effects of gestational weight gain (GWG) and hyperglycemia on adverse pregnancy outcomes suggest that lower optimal GWG is optimal for women with gestational diabetes mellitus (GDM). However, there is still a lack of guidelines. What is added by this report?Optimal weekly GWG range after diagnosis of GDM for underweight, normal-weight, overweight, and obese women was 0.37-0.56 kg/week, 0.26-0.48 kg/week, 0.19-0.32 kg/week, and 0.12-0.23 kg/week, respectively. What a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, studies must also consider the interaction of various complex factors on weight gain, such as GDM disease, pre-pregnancy weight, diet management, physical activity, and blood glucose levels (25,38). Lyu et al attempted to explore optimal GDM-related GWG based on Chinese populations, and found that giving GWG rates lower than IOM recommendations was beneficial to newborn birth weight (34). We must emphasize how crucial weight management is to the treatment of GDM disease and the well-being of women and children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies must also consider the interaction of various complex factors on weight gain, such as GDM disease, pre-pregnancy weight, diet management, physical activity, and blood glucose levels (25,38). Lyu et al attempted to explore optimal GDM-related GWG based on Chinese populations, and found that giving GWG rates lower than IOM recommendations was beneficial to newborn birth weight (34). We must emphasize how crucial weight management is to the treatment of GDM disease and the well-being of women and children.…”
Section: Discussionmentioning
confidence: 99%
“…Chakkalakal et al compared the lower weight gain after GDM diagnosis to delivery than women without GDM, indicating that GDM treatment can improve weight management of pregnant mothers (26). In addition, a cohort study from China reported an optimal GDM-related GWG rate for women with GDM and different pre-BMI with the goal of reducing adverse birth weight outcomes (34). The recommended range of optimal GWG rates provided by this study is lower than the range recommended by the IOM (Table 1).…”
Section: Management Objectives and Evaluation Methods Of Gdm-related Gwgmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is a common complication during pregnancy, posing significant health risks to both the fetus and the mother. The incidence of GDM has been rising, with reported rates ranging from 1% to 14% internationally and from 2% to 18% in China (1)(2)(3)(4). Additionally, the onset of GDM is occurring at increasingly younger ages (2).…”
Section: Introductionmentioning
confidence: 99%
“…Female GDM patients’ records from 2011 to 2021 were analyzed for this project. All information was extracted from electronic medical records, details of which have been discussed in a previous study ( 6 ). Subjects’ weights, usually not assessed during the 75-g oral glucose tolerance test (OGTT), were documented a week before or after the activity to obtain more comprehensive data.…”
mentioning
confidence: 99%
“…Essential data were collected from medical records, which included maternal age, weight prior to pregnancy, week of GDM diagnosis, weight at time of GDM diagnosis, weight before delivery, weeks remaining until delivery, and neonatal birth weight. The diagnostic criteria for GDM are the same as in previous study ( 6 ).…”
mentioning
confidence: 99%